2x-7+3x=11+x+2

Simple and best practice solution for 2x-7+3x=11+x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-7+3x=11+x+2 equation:


Simplifying
2x + -7 + 3x = 11 + x + 2

Reorder the terms:
-7 + 2x + 3x = 11 + x + 2

Combine like terms: 2x + 3x = 5x
-7 + 5x = 11 + x + 2

Reorder the terms:
-7 + 5x = 11 + 2 + x

Combine like terms: 11 + 2 = 13
-7 + 5x = 13 + x

Solving
-7 + 5x = 13 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-7 + 5x + -1x = 13 + x + -1x

Combine like terms: 5x + -1x = 4x
-7 + 4x = 13 + x + -1x

Combine like terms: x + -1x = 0
-7 + 4x = 13 + 0
-7 + 4x = 13

Add '7' to each side of the equation.
-7 + 7 + 4x = 13 + 7

Combine like terms: -7 + 7 = 0
0 + 4x = 13 + 7
4x = 13 + 7

Combine like terms: 13 + 7 = 20
4x = 20

Divide each side by '4'.
x = 5

Simplifying
x = 5

See similar equations:

| 4(3c-2)=9c-7 | | 5-3(2d+5)=2 | | 6d+5=11 | | .6666667q-2=.3333333q+7 | | y+25=40 | | (3x+10)+(7x-30)=180 | | 9-8.2= | | 9(2k+3)= | | 5x+4(3x-16)=140 | | -6x+40=-3x-11 | | 0.5x^2*x^2=0 | | 2x+8=4x-128 | | 6x^2-x+13=0 | | 47=w-8 | | 5p-17=2(-2p-7) | | 2[7-6(1-n)]+9n=-20+4[6(n+1)-3n] | | 4(x+6)=35 | | -10x-3(9-x)=4(-2+5)-12 | | 2(x+1)=38 | | 24-5m= | | 2[7-6(1-n)]+8n=-14+3[6(n+1)-3n] | | 0.5x*x=0 | | 6+3-x/2=1 | | -77-14y-2y=-13 | | (2-x)(12+4x)=(-4-2x)(24-2x) | | 6(x+2)=38 | | 6x+1=10-3x | | 6x+10y=6302 | | 2x=6x-15 | | 5m+8+4(3m-3)-3(m+3)=0 | | ln(2x+3)=2 | | -(6x-5)-(4x-5)+13=-11(x-1)-(4x+11)+3 |

Equations solver categories